The X-ray disc/wind degeneracy in AGN. Issue 1 (31st March 2022) - Parker, M L; Matzeu, G A; Matthews, J H; Middleton, M J; Dauser, T; Jiang, J; Joyce, A M
ABSTRACT: Relativistic Fe K emission lines from accretion discs and from disc winds encode key information about black holes, and their accretion and feedback mechanisms. We show that these two processes can in principle produce indistinguishable line profiles, such that they cannot be disentangled spectrally. We argue that it is likely that in many cases both processes contribute to the net line profile, and their relative contributions cannot be constrained purely by Fe K spectroscopy. In almost all studies of Fe K emission to date, a single process (either disc reflection or wind Compton scattering) is assumed to dominate the total line profile. We demonstrate that fitting a single process emission model (pure reflection or pure wind) to a hybrid line profile results in large systematic biases in the estimates of key parameters, such as mass outflow rate and spin. We discuss various strategies to mitigate this effect, such as including high-energy data covering the Compton hump, and the implications for future X-ray missions.